2021
DOI: 10.1108/jabs-07-2021-0316
|View full text |Cite
|
Sign up to set email alerts
|

Intensifying effects of COVID-19 on economic growth, logistics performance, environmental sustainability and quality management: evidence from Asian countries

Abstract: Purpose This study aims to explore the effects of the COVID-19 outbreak on exports of goods and services, logistics performance, environmental management system (ISO 14001) certification and quality management system (ISO 9001) certification in top affected Asian countries of India, Iran, Indonesia, Philippines, Bangladesh and Pakistan. Design/methodology/approach A novel grey relational analysis models’ approach is used to examine the inter-relationship between COVID-19 economic growth and environmental per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 57 publications
0
25
0
1
Order By: Relevance
“…Moreover, it influences the food supply chain around the world, as well as food production [4,5] and transportation capacity [7]. In the study conducted by [8], the top six Asian countries affected by COVID-19 on their exports and logistic performance include Pakistan, Bangladesh, Iran, India, Indonesia, and Philippines. The study found strong negative association of COVID-19 on exports and logistic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it influences the food supply chain around the world, as well as food production [4,5] and transportation capacity [7]. In the study conducted by [8], the top six Asian countries affected by COVID-19 on their exports and logistic performance include Pakistan, Bangladesh, Iran, India, Indonesia, and Philippines. The study found strong negative association of COVID-19 on exports and logistic performance.…”
Section: Introductionmentioning
confidence: 99%
“…So, maintaining a competitive advantage requires initiating positive changes in a diverse world regarding economic development and environmental degradation [81,82]. Ikram et al [83] research findings show that governments must take corrective measures to prevent the economies from more damages and improve their logistics, environmental…”
Section: Plos Onementioning
confidence: 99%
“…The fifth article evaluated the measures to mitigate the impacts of the COVID-19 pandemic through circular economy enablers and found that waste reduction and its transformation into a resource is the most important enabler for a sustainable and resilient supply chain (Agarwal et al , 2021). The sixth article analyzed the impacts of the COVID-19 pandemic on economic growth, logistics performance, environmental sustainability and quality management in the context of Asian countries and found that the COVID-19 pandemic had a substantial negative impact on business performances for all countries such as India, Iran, Indonesia, Philippines, Bangladesh and Pakistan (Ikram et al , 2021). The seventh article analyzed the key performance indicators (KPIs) of a healthcare supply chain and found that KPI-related strategies play a significant role in sustainable recovery from the impacts of the COVID-19 pandemic (Rahman et al , 2021b).…”
Section: Green Recovery Through Sustainable Supply Chains: Implicatio...mentioning
confidence: 99%